Increasing resistance of wheat to unfavorable environmental factors by pre-sown priming of its grains (Eurasian Journal of Ecology, 2018)
Presowing priming involves soaking seeds under controlled conditions until complete saturation with water or essential components for thefurther development of plants, seeds followed by drying. AO (aldehydeoxidase) is involved in ABA biosynthesis, converting abscisic aldehyde toABA. Seeds of resistent cultivar – NAZ, soaked in a solution of 50 mMmolybdate, showed high activity of AО1, indicating that the maximum saturation molybdenum enzyme. Saratovskaya- 29 was shown that soaked of theseeds in 50 mMmolybdate solution for 24 hours, as these optimal conditions hydrating seed will increase in ABA content of the caryopsis. Excessive ROS formed in the conditions of application of priming, in embryonictissues during hypoxia induces increasing synthesis of ABA. In seeds during soaked in 50 mMmolybdate solution increased ABA content in 10.5times of Lutecsens 70 and 5.2 times by soaking the seeds in water. As aresult of the priming procedure, which is accompanied by the formationof excess free radicals induced defensive responses in plant cells. Incubation of seeds within 24 hours and 32 hours during this period increasedGR activity and almost no imbalance reduced and oxidized glutathione,wheat varieties. Views will data showed that pre-sowing seed priming bothvarieties NAZ and Saratovskaya 29 led to an increase in the content ofendogenous ABA in 2 times and 1.5 times the antioxidants and as a resulthas led to an increase in resistance to stress (adverse environmental factors)both varieties.This paper presents the results of the impact of pre-sowing grain priming maintenance plant hormone ABA, the activity of AO and antioxidantenzymes in two different varieties of wheat.Key words: priming, wheat, ABA, AO, abiotic stress, antioxidants